2017
DOI: 10.1109/tuffc.2017.2713599
|View full text |Cite
|
Sign up to set email alerts
|

A Light Illumination Enhancement Device for Photoacoustic Imaging: In Vivo Animal Study

Abstract: Photoacoustic (PA) imaging detects acoustic signals generated by thermal expansion of a light-excited tissue or contrast agents. PA signal amplitude and image quality directly depend on the light fluence at the target depth. With conventional PA imaging systems, approximately 30% energy of incident light at the near-infrared region would be lost due to reflection on the skin surface. Such light loss directly leads to a reduction of PA signal and image quality. A new light delivery scheme that collects and redi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…One method used light reflectors on the transducer face or around the end of the optical fibers and transducer to reflect upwardly scattered light back into the tissue. 51,[64][65][66] However, experimental testing of the phenomena showed mixed results. When imaging arteries in mice in vivo, the reflector did not show the improvements found from modeling, 67 although curved reflectors have given better experimental results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One method used light reflectors on the transducer face or around the end of the optical fibers and transducer to reflect upwardly scattered light back into the tissue. 51,[64][65][66] However, experimental testing of the phenomena showed mixed results. When imaging arteries in mice in vivo, the reflector did not show the improvements found from modeling, 67 although curved reflectors have given better experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…When imaging arteries in mice in vivo, the reflector did not show the improvements found from modeling, 67 although curved reflectors have given better experimental results. 64,66 Periyasamy and Pramanik 51 also considered different arrangements of the fiber bundles around the US transducer. We also did not consider the variation in fluence along the imaging plane, as this has been found previously to vary little with the length of the optical fiber bundle, 23 nor did we consider the effect of offsetting the fiber bundle from the tissue surface as this has already been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Near-infrared light is desired for laser activation at sufficient depths while also allowing for deep PAI. Yu et al demonstrated PAI with a clinical photosensitizer, verteporfin, on a mouse tumor (34). Ho et al evaluated the photoacoustic efficacy of 5 different photosensitizers (35).…”
Section: Laser-activated Therapy With Guidance Of Paimentioning
confidence: 99%
“…In addition, there have been efforts to develop affordable PAI systems, such as replacing the bulky solidstate lasers with diode lasers or light-emitting diodes and integrating the light source and the detector into a handheld probe (37,38). In efforts to make PAI more suitable for freehand scanning in a clinical environment, a concavemirror-shaped device attached to the ultrasound probe was proposed to not only protect an operator and a patient from unwanted exposure to the reflected laser light but also improve the signal-to-noise-ratio for deep tissue imaging (34). Exogenous photoacoustic contrast agents also should be further evaluated under biologically relevant conditions to assess bioeffects and improve binding or treatment efficiency in situ.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…It is necessary to focus on the development of exogenous contrast agents based on biological materials for efficient translation of the multimodal PA imaging techniques into clinical practice for SLN identification and biopsy guidance. To increase the clinical usefulness, additionally, developing real-time methods for increasing light penetration is an important research topic [103,104], although PA imaging allows for a relatively deep imaging depth. This also make it possible to exploit (multimodal) PA imaging in various clinical applications.…”
Section: Implications For Future Researchmentioning
confidence: 99%